Relationship Between Housing Physical Conditions and the Incidence of Acute Respiratory Infections (ARI) Among Toddlers in Andalas Padang - Kalasta Ayunda Putri; Riyana Husna (CV. Get Press Indonesia, 2026)
Acute Respiratory Infection (ARI) remains a major health problem among children under five in Indonesia, including in Padang City. Poor housing physical conditions such as inadequate ventilation, insufficient natural lighting, high residential density, and improper humidity levels may increase the risk of ARI among toddlers. This study aimed to determine the relationship between housing physical conditions and the incidence of ARI among toddlers in Andalas Padang 2026. This study used an analytic observational design with a cross sectional approach. The study population consisted of mothers with toddlers aged 12–59 months in the Andalas, Padang City. A total of 80 respondents were selected using proportional random sampling technique. Data were collected through interviews, direct observation of housing conditions, and measurement of temperature, humidity, and lighting using environmental measuring instruments. Data were analyzed using univariate and bivariate analysis with the Chi-Square test at a 95% confidence level (α = 0.05). The results showed significant relationships between house ventilation (p-value = 0.004), natural lighting (p-value = 0.018), residential density (p-value = 0.001), and house humidity (p-value = 0.015) with the incidence of ARI among toddlers. Residential density was the variable most strongly associated with ARI incidence. In conclusion, housing physical conditions are associated with the incidence of ARI among toddlers. Therefore, efforts to improve healthy housing quality are needed to reduce ARI incidence among children under five